Role of Accounting Information in Decision Making in Co-Operative in Kirtipur Municipality, Kathmandu - Mahataman, Tribhuvan Kumar (Cognition, 2024)
The accounting information is used co-operative as well as business sectors. It makes easy to managerial and operational decision of an organization. The aim of this paper is to investigate the impact of accounting information on investment and marketing decision in co-operative in Kirtipur. Accounting information plays an important role in sustaining a competitive market. Rational investment and marketing decisions can save cooperatives from the present financial crisis. This research is quantitative in nature and deductive in approach. It followed field survey based on convenience sampling. SPSS was used to analyze the data collected from 60 usable questionnaires returned from respondents. The total population of the study is 96. The p-value is 0.000, which is less than 1% level of significance. So, the ANOVA table indicates that the model is fitted. There is a significant impact of accounting information on investment and marketing decisions. In the competitive age accounting information is important for investment and marketing related decision for survive and growth of co-operatives.